The Principle of Legality of the Administration - Rapajic, Milan M; Logarušić, Dejan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The contemporary administrative law is based on a set of legal principles which permeate all institutes of administrative law, giving them meaning and creating a harmonious whole. The first and most important pillar of the administrative law normative system is the principle of legality, which implies that the administration is subjected to the applicable laws. Administration is a creation of law; it is organized, regulated and acts in compliance with the law. The basic function of the administration is to implement the laws by observing the law in force. It cannot perform its functions beyond the limits set by the law, nor contrary to the law. In all modern states, the principle of legality in general, and the principle of legality of administration in particular, are the cornerstone for the development of the rule of law. The principle of legality rests on the legal activities of the administration. Under the constitution and the law, administration has a dual role: to adopt a specific administrative legislative act, and to adopt of a normative act (by-law). The concept of legality applied to an administrative act implies that it is impermissible to use coercive means without a justifiable legal ground, which stems from the executive character of an authoritative act which unilaterally determines the parties’ rights and obligations. In this sense, the legality of an administrative act must include all its essential elements: jurisdiction, form, basic rules of procedure, purpose, and even substantive law issues. When it comes to normative acts, the principle of legality works in two directions: existential and substantive. The paper presents the concept and the content of the principle of legality of the administration, the relationship between the principle of legality and discretionary assessment, as well as the relationship between the principle of legality and the principle of proportionality, as one of the more recent principles in European continental public law. The authors outline the typical violations of the principle of legality and sanctions for those violations.